Soft carbon and preparation method thereof

By blending low-sulfur residue oil, catalytic cracking oil slurry and hydrogenation oil, and adding organic nitrogen, soft carbon materials are prepared by in-situ doping technology, the problem of insufficient capacity and efficiency of existing soft carbon materials is solved, and high capacity and high efficiency preparation of soft carbon materials is achieved. The process is simple, the cost is low, and it is suitable for industrial production.

CN119898755APending Publication Date: 2025-04-29HAIKE GRP RES INST OF INNOVATION & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510116955.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing soft carbon anode materials have shortcomings in capacity and first-time Coulomb efficiency, and the preparation process is complex and costly, making it difficult to be suitable for industrial production.

Method used

Low-sulfur residue oil, catalytic cracking oil slurry and hydrogenation oil are used to blend, organic nitrogen is added as the nitrogen source, and graphite nitrogen content is increased during the carbonization process through in-situ doping technology, and high-capacity soft carbon materials are prepared in combination with appropriate heat treatment and coking treatment.

Benefits of technology

The capacity of soft carbon materials is ≥425mAh/g and the first Coulomb efficiency is ≥80%, while the preparation process is simplified, the cost is reduced, and it is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898755A_ABST
    Figure CN119898755A_ABST
Patent Text Reader

Abstract

The invention provides soft carbon and a preparation method thereof, and belongs to the technical field of preparation of soft carbon negative electrode materials. The preparation method of the soft carbon comprises the following steps: 1) blending one or more of low-sulfur residual oil, catalytic cracking oil slurry and hydrogenated oil to obtain a blended material; 2) carrying out heat treatment on the blended material to obtain a pretreated material; 3) mixing organic nitrogen with the pretreated material, and carrying out heat treatment under inert atmosphere protection to obtain a mixed material; 4) carrying out coking treatment on the mixed material under the protection of an inert atmosphere to obtain green coke for soft carbon; and 5) sequentially carrying out pre-carbonization treatment and carbonization treatment on the soft carbon by using green coke under the protection of an inert atmosphere to obtain the soft carbon. The method provided by the invention is simple in process, the capacity of the prepared soft carbon is greater than or equal to 425mAh / g, and the first coulombic efficiency is greater than or equal to 80%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soft carbon negative electrode material preparation, and in particular relates to soft carbon and a preparation method thereof. Background Art

[0002] Since soft carbon negative electrode materials have a larger interlayer spacing (d002), they have excellent rate performance compared to graphite materials. They are also highly adaptable to electrolytes, resistant to overcharge and overdischarge, and have excellent cycle performance. However, the capacity and first coulombic efficiency of soft carbon negative electrode materials currently prepared are relatively low, so there is still a lot of room for development in the capacity of soft carbon materials.

[0003] Chinese patent CN103050699A discloses a method for preparing a soft carbon negative electrode material for a lithium ion battery, comprising the following steps: mixing a catalyst with asphalt; heating to 180-380°C and reacting for at least 0.7 hours; heating to 320-600°C and reacting for at least 0.3 hours to obtain a mesophase spherical primary product; removing impurities from the mesophase spherical primary product and drying it to obtain a soft carbon-like carbon microsphere mesophase precursor; mixing the soft carbon-like carbon microsphere mesophase precursor with a nitrogen-containing compound and / or a boron-containing compound and allowing it to stand; heating to 400-1600°C under a protective atmosphere and performing pyrolysis treatment for at least 0.6 hours to obtain a soft carbon negative electrode material. Although the invented material greatly reflects the capacity of existing soft carbon materials, the preparation process is complicated and the cost of industrial production is high, which is not conducive to industrial production. CN102428594A discloses a phosphorus and boron co-doped coke-like carbon material and a preparation method thereof. Although the capacity of coke-like soft carbon is improved, the energy density is low when used alone as a negative electrode material for power batteries due to its high average voltage and low compaction density. Therefore, developing a high-capacity soft carbon with a simple production process and low cost is a technical problem in the field. Summary of the invention

[0004] The invention provides a soft carbon and a preparation method thereof. The method provided by the invention has a simple process, and the prepared soft carbon has a capacity of ≥425 mAh / g and a first coulombic efficiency of ≥80%.

[0005] In order to achieve the above object, the present invention provides a method for preparing soft carbon, comprising the following steps:

[0006] 1) blending one or more of low-sulfur residual oil, catalytic cracking oil slurry and hydrogenated oil to obtain a blended material; in terms of weight percentage, the blended material contains 5-10% asphaltene, 15-30% colloid, 30-41% aromatic fraction and 25-40% saturated fraction;

[0007] 2) heat-treating the blended material to obtain a pretreated material;

[0008] 3) mixing the organic nitrogen with the pretreated material, and performing a heat treatment under the protection of an inert atmosphere to obtain a mixed material;

[0009] 4) coking the mixed material under the protection of an inert atmosphere to obtain green coke for soft carbon;

[0010] 5) The soft carbon raw coke is subjected to a pre-carbonization treatment and a carbonization treatment in sequence under the protection of an inert atmosphere to obtain soft carbon.

[0011] Preferably, by weight percentage, the sulfur content of the low-sulfur residual oil in step 1) is 0.1% to 2.0%; the sulfur content of the catalytic cracking slurry is 0.1% to 2.0%.

[0012] Preferably, step 1) further comprises adding asphalt before blending; the amount of asphalt added is 3-10% of the total mass of the blended material.

[0013] Preferably, the temperature of the heat treatment in step 2) is 100-150° C. and the time is 30-60 min.

[0014] Preferably, the temperature of the heat treatment in step 3) is 100-200° C. and the time is 30-180 min.

[0015] Preferably, in terms of weight percentage, the organic nitrogen in step 3) is 2-30% of the total mass of the mixed material; the organic nitrogen is melamine and / or polyacrylonitrile.

[0016] Preferably, the temperature of the coking treatment in step 4) is 420-500°C and the time is 3-36h; the optical structure of the coked product is a state in which a mosaic structure and a small domain structure coexist, wherein the mosaic structure accounts for ≥30%.

[0017] Preferably, the temperature of the pre-carbonization treatment in step 5) is 500-890° C., and the time is 1-5 h; the temperature of the carbonization treatment is 900-1500° C., and the time is 1-5 h.

[0018] Preferably, step 5) further comprises screening the green coke into coarse powder before pre-carbonization treatment; the mesh number of the screening is 2 to 200 meshes; and screening the green coke into fine powder after carbonization treatment; the mesh number of the fine powder screening is 210 to 2000 meshes.

[0019] The present invention also provides soft carbon prepared by any one of the above methods, wherein the soft carbon has a performance capacity of ≥425 mAh / g and a first coulombic efficiency of ≥80%.

[0020] Compared with the prior art, the advantages and positive effects of the present invention are:

[0021] (1) The present invention adopts an in-situ doping method to introduce pyrrolic nitrogen, pyridinic nitrogen or graphitic nitrogen into the intermediate phase. The carbonization process increases the graphitic nitrogen content. The defect sites produced can effectively reduce the mass transfer resistance of lithium ions. The graphitic nitrogen is beneficial to increase the π electron cloud density and the electronic conductivity of the carbon material. At the same time, the in-situ doping method ensures the consistency of the prepared product, and ultimately ensures that the product has excellent electrochemical properties.

[0022] (2) The nitrogen source provided by the present invention is an organic nitrogen-containing compound, which can be regarded as a hard carbon source. The carbonization process increases the disorder of the microcrystals, which can effectively increase the defective lithium storage space of the soft carbon material;

[0023] (3) The oil slurry ratio provided by the present invention is combined with a suitable organic nitrogen source and a suitable process to adjust the microcrystalline structure of the green coke product: the optical structure is a state where a mosaic structure and a small domain structure coexist, wherein the mosaic structure accounts for ≥30%, and the first effect is 80% or more;

[0024] (4) Due to the introduction of nitrogen-containing organic compounds at the raw material end, compared with raw coke of other structures, the nitrogen-containing organic matter can be embedded in the raw coke skeleton as a carbon skeleton during the coking process. During the carbonization process, N migration and discharge occur in the skeleton, and defects can be created at the microscopic and macroscopic levels, thereby increasing the active sites and space for storing lithium after carbonization, and the capacity is 425-450 mAh / g.

[0025] (5) The preparation method of high-performance soft carbon and raw materials provided by the present invention has simple process, low cost and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a scanning electron microscope image of the raw coke prepared in Example 1;

[0027] Figure 2 This is the polarization image of the raw focus prepared in Example 1;

[0028] Figure 3 This is a scanning electron microscope image of the raw coke prepared in Example 2;

[0029] Figure 4 This is the polarization image of the raw focus prepared in Example 2;

[0030] Figure 5 This is a scanning electron microscope image of the raw coke prepared in Example 3;

[0031] Figure 6 Polarization image of the raw coke prepared in Example 3;

[0032] Figure 7 This is a scanning electron microscope image of the raw coke prepared in Example 4;

[0033] Figure 8 This is the polarization image of the raw coke prepared in Example 4;

[0034] Fig. 9 This is an electron microscope scanning image of the raw coke prepared in Comparative Example 1;

[0035] Fig.10 This is a scanning electron microscope image of the raw coke prepared in Comparative Example 2;

[0036] Fig.11 This is a scanning electron microscope image of the raw coke prepared in Comparative Example 3;

[0037] Fig.12 This is a scanning electron microscope image of the raw coke prepared in Comparative Example 4;

[0038] Fig.13 This is a scanning electron microscope image of the raw coke prepared in Comparative Example 5;

[0039] Fig.14 is a charge and discharge curve diagram of the soft carbon of Example 1;

[0040] Fig.15 is a charge and discharge curve diagram of the soft carbon of Example 2;

[0041] Fig.16 is a charge and discharge curve diagram of the soft carbon of Example 3;

[0042] Fig.17 This is the charge and discharge curve of the soft carbon of Example 4. DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] The present invention provides a method for preparing soft carbon, comprising the following steps:

[0045] 1) blending one or more of low-sulfur residual oil, catalytic cracking oil slurry and hydrogenated oil to obtain a blended material; in terms of weight percentage, the blended material contains 5-10% asphaltene, 15-30% colloid, 30-41% aromatic fraction and 25-40% saturated fraction;

[0046] 2) heat-treating the blended material to obtain a pretreated material;

[0047] 3) mixing the organic nitrogen with the pretreated material, and performing a heat treatment under the protection of an inert atmosphere to obtain a mixed material;

[0048] 4) coking the mixed material under the protection of an inert atmosphere to obtain green coke for soft carbon;

[0049] 5) The soft carbon raw coke is subjected to a pre-carbonization treatment and a carbonization treatment in sequence under the protection of an inert atmosphere to obtain soft carbon.

[0050] The present invention blends one or more of low-sulfur residual oil, catalytic cracking slurry and hydrogenated oil to obtain a blended material; by weight percentage, the asphaltene ratio in the blended material is 5-10%, the colloid ratio is 15-30%, the aromatic fraction ratio is 30-41%, and the saturated fraction ratio is 25-40%. In the present invention, by weight percentage, the sulfur content in the low-sulfur residual oil is preferably 0.1%-2.0%; the sulfur content in the catalytic cracking slurry is preferably 0.1%-2.0%. In the present invention, it is preferred to add asphalt before blending; the addition amount of the asphalt is preferably 3-10% of the total mass of the blended material. In the present invention, the addition of asphalt can serve as a crystal nucleus for the development of the mesophase, further increasing the number of mesophase globules. In the present invention, it is preferred to also filter before blending. In the present invention, the aperture of the filter screen for filtration is preferably 10-100 meshes. In the present invention, filtration can reduce the solid content, remove ash metal residues, and improve the oil slurry yield.

[0051] The present invention has no special restrictions on the sources of the low-sulfur residual oil, catalytic cracking oil slurry, hydrogenated oil and asphalt, and conventional products in the field can be used. The low-sulfur residual oil, catalytic cracking oil slurry, hydrogenated oil and asphalt in the examples and comparative examples of the present invention are produced by Sinopec, Dongying Petrochemical, Haike Yiwei and Hezheng Company respectively.

[0052] After obtaining the blended material, the present invention heat treats the blended material in air to obtain a pretreated material. In the present invention, the temperature during the heat treatment is preferably 100 to 150° C., and the time is preferably 30 to 60 minutes. In the present invention, heat treatment of the blended material helps to uniformly mix the oil slurries of each component.

[0053] After obtaining the pretreated material, the present invention mixes organic nitrogen with the pretreated material, performs heat treatment under the protection of an inert atmosphere, and obtains a mixed material. In the present invention, the organic nitrogen is preferably 2 to 30% of the total mass of the mixed material; the organic nitrogen is preferably melamine and / or polyacrylonitrile. In the present invention, the above-mentioned organic nitrogen can be regarded as a hard carbon source, and the carbonization process can increase the disorder of the microcrystals, which can effectively increase the defective lithium storage space of the soft carbon material. In the present invention, the temperature during the heat treatment is preferably 100 to 200°C, and the time is preferably 30 to 180 minutes. In the present invention, the heat treatment process is conducive to the full dispersion of organic nitrogen in the oil slurry.

[0054] After obtaining the mixed material, the present invention performs a coking treatment on the mixed material under the protection of an inert atmosphere to obtain green coke for soft carbon. In the present invention, the temperature during the coking treatment is preferably 420-500°C, and the time is preferably 3-36 hours; the optical structure of the green coke is a state in which a mosaic structure and a small domain structure coexist, wherein the mosaic structure accounts for ≥30%. In the present invention, the mosaic structure refers to a same-color area size of ≤10μm in a polarized image, and the small domain structure refers to a same-color area size of 10-30μm in a polarized image.

[0055] After obtaining the green coke for soft carbon, the present invention sequentially performs pre-carbonization treatment and carbonization treatment on the green coke for soft carbon under the protection of an inert atmosphere to obtain soft carbon. In the present invention, the green coke is also screened for coarse powder before the pre-carbonization treatment; the mesh number of the coarse powder screening is 2 to 200 meshes. After the carbonization treatment, it is preferred to further perform fine powder screening; the mesh number of the fine powder screening is 210 to 2000 meshes. In the present invention, the particle size can be controlled in advance by screening the green coke for coarse powder, and particles can be prevented from sticking during the pre-carbonization process. In the present invention, the temperature of the pre-carbonization treatment is preferably 500 to 890°C, and the time is preferably 1 to 5 hours; the temperature during the carbonization treatment is preferably 900 to 1500°C, and the time is preferably 1 to 5 hours. In the present invention, pre-carbonization is first performed at 500-890°C, and then the temperature is raised to 900-1500°C for carbonization, which can ensure the controllability of the growth of soft carbon microcrystals and reduce the overflow of volatiles and the pollution of high-temperature equipment. In the pre-carbonization process of the present invention, the particle size control range is 2-200 mesh, the volatiles are quickly released during the pre-carbonization process, a large number of defect sites appear, the raw material microcrystals develop slowly, and the particles can be prevented from sticking together; after pre-carbonization, the particles are crushed and sieved to 210-2000 mesh, and high-temperature carbonization is performed, and the raw material carbon microcrystals develop rapidly.

[0056] The present invention is based on the analysis of the aromatic composition of low-sulfur residual oil, FCC cracking oil slurry and hydrogenated oil, and utilizes the differences in the intermediate phases of different aromatic components and the coking process to control the development structure of coke used as soft carbon raw material. In addition, an organic nitrogen source is added to the intermediate phase by in-situ doping, and pyrrole nitrogen, pyridine nitrogen or graphite nitrogen is introduced. The carbonization process increases the content of graphite nitrogen, and the defect potentials produced can effectively reduce the mass transfer resistance of lithium ions. Graphitized nitrogen is conducive to increasing the π electron cloud density and improving the electronic conductivity of carbon materials. In addition, the added organic nitrogen-containing compound can be regarded as a hard carbon carbon source, and the carbonization process increases the disorder of microcrystals, which can effectively increase the defect lithium storage space of soft carbon materials. Due to the introduction of nitrogen-containing organic compounds at the raw material end, the present invention has an increase in active sites and space for storing lithium after carbonization compared to coke with other structures, and the capacity is 425-450mAh / g. The present invention directly adds nitrogen-containing organic matter into the oil slurry and directly performs coking by controlling the pressure and temperature in a heating furnace. The process is simple and feasible, the product yield is high, and the product consistency and stability are high. In addition, the preparation process of the method is green and pollution-free, the cost is low, and it is suitable for industrial production.

[0057] The present invention also provides soft carbon prepared by any one of the above methods, wherein the soft carbon has a performance capacity of ≥425 mAh / g and a first coulombic efficiency of ≥80%.

[0058] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0059] Example 1

[0060] The low-sulfur residual oil, catalytic cracking slurry and industrial hydrogenated oil were filtered separately. After filtering, the low-sulfur residual oil (sulfur content 0.4%), catalytic cracking slurry (sulfur content 2.0%) and industrial hydrogenated oil were blended in a mass ratio of 8:2:1. The asphaltene ratio in the blended material was 6.84%, the gum ratio was 22.51%, the aromatic fraction was 38.89%, and the saturated fraction was 31.76%. In an air atmosphere, the obtained blended material was heated at 150°C in a heating furnace for 60 minutes to obtain a pretreated material. Melamine was added to the pretreated material at a mass ratio of 10%, nitrogen was introduced and the agitator was turned on, and the mixture was heated and stirred at 120°C for 60 minutes to obtain a mixed material. The obtained mixed material was coked at 470°C for 24 hours under a nitrogen atmosphere to obtain green coke. The prepared green coke product was subjected to electron microscope scanning and polarization tests, and the specific results are as follows: Figure 1 and 2 As shown. Figure 1 and 2 It can be seen that the prepared green coke has poor orientation, a compact structure, a large number of wrinkles and mosaic structures, and an obvious layered structure on the particle surface.

[0061] The obtained green coke was crushed and sieved to a particle size of 2.5 mm (D50), and calcined at 600℃ in a nitrogen atmosphere for 3 hours. The obtained pre-carbonized material was crushed and sieved to a particle size of 10 microns (D50), and then the nitrogen furnace was heated to 1100℃ and calcined for 3 hours to obtain high-performance soft carbon. The charge and discharge curve of the soft carbon is shown in the figure. Fig.14 shown.

[0062] Example 2

[0063] The low-sulfur residual oil, catalytic cracking slurry and industrial hydrogenated oil were filtered separately. After filtering, the low-sulfur residual oil (sulfur content 0.4%), catalytic cracking slurry (sulfur content 2.0%) and industrial hydrogenated oil were blended in a mass ratio of 1:1:1. The asphaltene ratio, the gum ratio, the aromatic fraction ratio and the saturated fraction ratio were 8.2%, 25.18%, 40.68% and 25.94% in the blended material. In an air atmosphere, the obtained blended material was heat-treated at 150°C for 30 minutes in a heating furnace to obtain a pretreated material. Polyacrylonitrile was added to the pretreated material at a mass ratio of 10%, nitrogen was introduced and the agitator was turned on, and the mixture was heated and stirred at 100°C for 45 minutes to obtain a mixed material. The obtained mixed material was coked at 500°C for 12 hours to obtain green coke. The prepared green coke product was subjected to electron microscope scanning and polarization tests, and the specific results are as follows. Figure 3 and 4 As shown. Figure 3 and 4 It can be seen that the prepared green coke has poor orientation, a tight structure, and a large number of wrinkles and mosaic structures.

[0064] The obtained green coke was crushed and sieved to a particle size of 2.5 mm (D50), and calcined at 800℃ in a nitrogen atmosphere for 3 hours. The obtained pre-carbonized material was crushed and sieved to a particle size of 10 microns (D50), and then heated to 1000℃ in a nitrogen furnace for 2 hours to obtain high-performance soft carbon. The charge and discharge curve of the soft carbon is shown in the figure. Fig.15 shown.

[0065] Example 3

[0066] The low-sulfur residual oil, catalytic cracking slurry and industrial hydrogenated oil were filtered separately. After filtering, the catalytic cracking slurry (sulfur content of 0.8%) and low-sulfur residual oil (sulfur content of 0.4%) were blended at a mass ratio of 8:1. The asphaltene ratio, the gum ratio, the aromatic fraction, and the saturated fraction were 9.64%, 23.95%, 40.26%, and 26.15% in the blended material. In an air atmosphere, the obtained blended material was treated at 120°C in a heating furnace for 45 minutes to obtain a pretreated material. Polyacrylonitrile was added to the pretreated material at a mass ratio of 2%, a nitrogen atmosphere was introduced, the stirrer was turned on, and the mixture was heated and stirred at 200°C for 30 minutes. The obtained mixture was coked at 420°C for 36 hours to obtain raw coke. The prepared product was subjected to electron microscope scanning and polarization tests, and the specific results are as follows. Figure 5 and 6 As shown. Figure 5 and 6 It can be seen that the orientation degree of the prepared green coke is also poor, the structure is very tight, and there are many flaky structures.

[0067] The obtained raw coke was crushed and sieved to a particle size of 2.5 mm (D50), and calcined at 900℃ in a nitrogen atmosphere for 3 hours. The obtained pre-carbonized material was crushed and sieved to a particle size of 10 microns (D50), and the temperature was raised to 1500℃ in a nitrogen furnace and treated for 1 hour to obtain high-performance soft carbon. The charge and discharge curve of the soft carbon is shown in the figure. Fig.16 shown.

[0068] Example 4

[0069] The catalytic cracking oil slurry is filtered. After filtering, the catalytic cracking oil slurry (sulfur content is 0.8%) and asphalt (the amount of asphalt added is 3% of the mass of the catalytic cracking oil slurry) are mixed, and treated at 150°C for 30 minutes in a heating furnace to obtain a pretreated material. Polyacrylonitrile is added to the pretreated material at a mass ratio of 30%, an inert atmosphere is introduced, the stirrer is turned on, and heating and stirring are performed at 120°C for 180 minutes. The obtained mixture is coked at 470°C for 3 hours to obtain raw coke. The prepared product was subjected to electron microscope scanning and polarization testing. The specific results are as follows Figure 7 and 8 As shown. Figure 7 and 8 It can be seen that the prepared green coke has a poor orientation, a tight structure, some wrinkles and mosaic structures, and a large number of fine particles attached to the surface of the particles.

[0070] The obtained green coke was crushed and sieved to a particle size of 2.5 mm (D50), and calcined at 500℃ in a nitrogen atmosphere for 3 hours. The obtained pre-carbonized material was crushed and sieved to a particle size of 10 microns (D50), and then heated to 1000℃ in a nitrogen furnace for 5 hours to obtain high-performance soft carbon. The charge and discharge curve of the soft carbon is shown in the figure. Fig.17shown.

[0071] Comparative Example 1

[0072] The difference from Example 2 is that polyacrylonitrile is not added, and the other operations are exactly the same as those in Example 1. The specific operations are as follows:

[0073] The low-sulfur residual oil, catalytic cracking slurry and industrial hydrogenated oil are filtered separately. After filtering, the low-sulfur residual oil (sulfur content 0.4%), catalytic cracking slurry (sulfur content 2.0%) and industrial hydrogenated oil are blended in a mass ratio of 1:1:1. The asphaltene ratio, the gum ratio, the aromatic fraction ratio and the saturated fraction ratio are 8.2%, 25.18%, 40.68% and 25.94% in the blended material. The obtained blended material is heat-treated at 150°C for 30 minutes in an air atmosphere to obtain a pretreated material. Nitrogen is introduced into the agitator and heated and stirred at 100°C for 45 minutes. Then the coking treatment is carried out at 500°C for 12 hours to obtain raw coke. The prepared product is scanned by electron microscope, and the specific results are as follows. Fig. 9 As shown. Fig. 9 It can be seen that the orientation of the prepared green coke is poor, and the layered structure of the particle surface is obvious.

[0074] The obtained raw coke is crushed and sieved to a particle size of 2.5 mm (D50), and calcined at 800°C in a nitrogen atmosphere for 3 hours. The obtained pre-carbonized material is crushed and sieved to a particle size of 10 microns (D50), and then heated to 1000°C in a nitrogen furnace for 2 hours to obtain high-performance soft carbon.

[0075] Comparative Example 2

[0076] The difference from Example 3 is that no polyacrylonitrile is added, and the other operations are exactly the same as those in Example 3. The specific operations are as follows:

[0077] The low-sulfur residual oil, catalytic cracking oil slurry and industrial hydrogenated oil are filtered separately. After filtering, the catalytic cracking oil slurry (sulfur content is 0.8%) and low-sulfur residual oil (sulfur content is 0.4%) are blended in a mass ratio of 8:1. The asphaltene ratio, the gum ratio, the aromatic fraction ratio and the saturated fraction ratio are 9.64%, 23.95%, 40.26% and 26.15% in the blended material. The obtained blended material is treated in an air atmosphere at 120°C in a heating furnace for 45 minutes to obtain a pretreated material. A nitrogen atmosphere is introduced and the agitator is turned on, and the mixture is heated and stirred at 200°C for 30 minutes. Then the mixture is coked at 420°C for 36 hours to obtain raw coke. The prepared product is scanned by an electron microscope, and the specific results are as follows. Fig.10 As shown. Fig.10 It can be seen that the orientation of the prepared green coke is general, the structure is loose, and the layered structure of the particle surface is obvious.

[0078] The obtained green coke is crushed and sieved to a particle size of 2.5 mm (D50), and calcined at 900°C in a nitrogen atmosphere for 3 hours. The obtained pre-carbonized material is crushed and sieved to a particle size of 10 microns (D50), and the temperature is raised to 1500°C in a nitrogen furnace and treated for 1 hour to obtain high-performance soft carbon.

[0079] Comparative Example 3

[0080] The difference from Example 4 is that no polyacrylonitrile is added, and the other operations are exactly the same as those in Example 4. The specific operations are as follows:

[0081] The catalytic cracking oil slurry was filtered. After filtering, the catalytic cracking oil slurry (sulfur content of 0.8%) and asphalt (the amount of asphalt added was 3% of the mass of the catalytic cracking oil slurry) were mixed and treated at 150°C for 30 minutes in a heating furnace to obtain a pretreated material. Heated and stirred at 120°C for 180 minutes. Then coking was performed at 470°C for 3 hours to obtain raw coke. The prepared product was scanned by electron microscope, and the specific results are as follows: Fig.11 As shown. Fig.11 It can be seen that the prepared green coke has poor orientation, a compact structure, and an obvious flaky structure on the particle surface.

[0082] The obtained raw coke is crushed and sieved to a particle size of 2.5 mm (D50), and calcined at 500°C in a nitrogen atmosphere for 3 hours. The obtained pre-carbonized material is crushed and sieved to a particle size of 10 microns (D50), and then heated to 1000°C in a nitrogen furnace for 5 hours to obtain high-performance soft carbon.

[0083] Comparative Example 4

[0084] The difference from Example 2 is that polyacrylonitrile is replaced by boric acid, and the other operations are exactly the same as those in Example 2. The specific operations are as follows:

[0085] The low-sulfur residual oil, catalytic cracking slurry and industrial hydrogenated oil were filtered separately. After filtering, the low-sulfur residual oil (sulfur content 0.4%), catalytic cracking slurry (sulfur content 2.0%) and industrial hydrogenated oil were blended in a mass ratio of 1:1:1. The asphaltene ratio, the gum ratio, the aromatic fraction ratio and the saturated fraction ratio were 8.2%, 25.18%, 40.68% and 25.94% in the blended material. The obtained blended material was heat-treated at 150°C for 30 minutes in an air atmosphere to obtain a pretreated material. Boric acid was added to the pretreated material at a mass ratio of 10%, nitrogen was introduced and the agitator was turned on, and the mixture was heated and stirred at 100°C for 45 minutes to obtain a mixed material. The obtained mixed material was coked at 500°C for 12 hours to obtain raw coke. The prepared product was scanned by electron microscope, and the specific results are as follows: Fig.12 As shown. Fig.12 It can be seen that the surface of the prepared green coke has a hollow structure and a large number of fine particles are attached.

[0086] The obtained raw coke is crushed and sieved to a particle size of 2.5 mm (D50), and calcined at 800°C in a nitrogen atmosphere for 3 hours. The obtained pre-carbonized material is crushed and sieved to a particle size of 10 microns (D50), and then heated to 1000°C in a nitrogen furnace for 2 hours to obtain high-performance soft carbon.

[0087] Comparative Example 5

[0088] The difference from Example 2 is that polyacrylonitrile is replaced by urea, and the other operations are exactly the same as those in Example 2. The specific operations are as follows:

[0089] The low-sulfur residual oil, catalytic cracking slurry and industrial hydrogenated oil were filtered separately. After filtering, the low-sulfur residual oil (sulfur content 0.4%), catalytic cracking slurry (sulfur content 2.0%) and industrial hydrogenated oil were blended in a mass ratio of 1:1:1. The asphaltene ratio, the gum ratio, the aromatic fraction ratio and the saturated fraction ratio were 8.2%, 25.18%, 40.68% and 25.94% in the blended material. The obtained blended material was heat-treated at 150°C for 30 minutes in a heating furnace to obtain a pretreated material. Urea was added to the pretreated material at a mass ratio of 10%, nitrogen was introduced and the agitator was turned on, and the mixture was heated and stirred at 100°C for 45 minutes to obtain a mixed material. The obtained mixed material was coked at 500°C for 12 hours to obtain raw coke. The prepared product was scanned by an electron microscope, and the specific results are as follows: Fig.13 As shown. Fig.13 It can be seen that the orientation of the prepared green coke is poor, and fine particles are attached to the surface of the particles.

[0090] The obtained raw coke is crushed and sieved to a particle size of 2.5 mm (D50), and calcined at 800°C in a nitrogen atmosphere for 3 hours. The obtained pre-carbonized material is crushed and sieved to a particle size of 10 microns (D50), and then heated to 1000°C in a nitrogen furnace for 2 hours to obtain high-performance soft carbon.

[0091] Performance Testing

[0092] The performance tests were performed on the soft carbon prepared in the examples and comparative examples. The specific operations are as follows:

[0093] The soft carbon obtained in each embodiment and comparative example was fully mixed with a binder and carbon black in a mass ratio of 94.5:4:1.5, and N-methylpyrrolidone (NMP) was added to prepare a negative electrode slurry, which was then evenly coated on a copper foil, dried, and rolled into a circular electrode sheet with a diameter of 14 mm. The electrode sheet was vacuum dried at 110° C. for 12 h, and then the battery was assembled in a glove box filled with argon, with metallic lithium as the counter electrode.

[0094] The charge and discharge capacity test was carried out on the Land battery test system. The charge and discharge voltage range was 0.005V to 2V, and the current density was 35mA / g. The specific charge and discharge performance is shown in Table 1.

[0095] Table 1

[0096]

[0097]

[0098] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing soft carbon, characterized in that: The steps include: 1) blending one or more of low-sulfur residual oil, catalytic cracking oil slurry and hydrogenated oil to obtain a blended material; in terms of weight percentage, the blended material contains 5-10% asphaltene, 15-30% colloid, 30-41% aromatic fraction and 25-40% saturated fraction; 2) heat-treating the blended material to obtain a pretreated material; 3) mixing the organic nitrogen with the pretreated material, and performing a heat treatment under the protection of an inert atmosphere to obtain a mixed material; 4) coking the mixed material under the protection of an inert atmosphere to obtain green coke for soft carbon; 5) The soft carbon raw coke is subjected to a pre-carbonization treatment and a carbonization treatment in sequence under the protection of an inert atmosphere to obtain soft carbon.

2. The preparation method according to claim 1, characterized in that: Calculated by weight percentage, the sulfur content in the low-sulfur residual oil in step 1) is 0.1% to 2.0%; the sulfur content in the catalytic cracking slurry is 0.1% to 2.0%.

3. The preparation method according to claim 1, characterized in that: Step 1) also includes adding asphalt before blending; the amount of asphalt added is 3-10% of the total mass of the blended materials.

4. The preparation method according to claim 1, characterized in that: The temperature of the heat treatment in step 2) is 100-150° C. and the time is 30-60 min.

5. The preparation method according to claim 1, characterized in that: The temperature of the heat treatment in step 3) is 100-200°C and the time is 30-180 minutes.

6. The preparation method according to claim 1, characterized in that: In terms of weight percentage, the organic nitrogen in step 3) is 2-30% of the total mass of the mixed material; the organic nitrogen is melamine, polyurethane and / or polyacrylonitrile.

7. The preparation method according to claim 1, characterized in that: The temperature of the coking treatment in step 4) is 420-500° C. and the time is 3-36 hours; the optical structure of the coked product is a state in which a mosaic structure and a small domain structure coexist, wherein the mosaic structure accounts for ≥30%.

8. The preparation method according to claim 1, characterized in that: The temperature of the pre-carbonization treatment in step 5) is 500-890°C, and the time is 1-5h; the temperature of the carbonization treatment is 900-1500°C, and the time is 1-5h.

9. The preparation method according to claim 1, characterized in that: Step 5) further comprises screening the green coke into coarse powder before pre-carbonization treatment; the mesh number of the screening is 2 to 200 meshes; and screening the green coke into fine powder after carbonization treatment; the mesh number of the fine powder screening is 210 to 2000 meshes.

10. Soft carbon prepared by the method according to any one of claims 1 to 9, characterized in that: The soft carbon has a performance capacity of ≥425 mAh / g and a first coulombic efficiency of ≥80%.

Citation Information

Patent Citations

  • Anode active material for lithium secondary batteries, anode electrode for lithium secondary batteries, in-vehicle lithium secondary battery using said anode active material and anode electrode, and method for manufacturing an anode active material for lithium secondary batteries

    CN102428594A

  • Soft carbon negative electrode material of lithium ion battery and preparation method thereof

    CN103050699A